Factors Associated with Nurses' Job Satisfaction in the Implementation of the Team Assignment Method - Rahmawati, Anisa Ayu (Genius Journal, 2025)
Introduction: The implementation of team-based nursing assignments is increasingly recognized as a crucial factor influencing nurses' job satisfaction. However, the effectiveness of this method in enhancing job satisfaction remains insufficiently explored, especially in Indonesian hospital settings. Objective: This study aimed to identify the factors related to nurses' job satisfaction in relation to the application of the team assignment method at Bhayangkara Hospital, Bandar Lampung in 2025. Method: This quantitative research employed a cross-sectional design involving 55 nurses selected using purposive sampling. The population included all inpatient nurses, with sample distribution determined using stratified random sampling. Data were analyzed using statistical tests to examine the association between job satisfaction factors (responsibility, working conditions, coworker relations, and task assignment) and the implementation of the team method. Results: The findings showed significant relationships between the team assignment method and all measured aspects of job satisfaction. Nurses with good responsibility, favorable working conditions, positive coworker relations, and clear task assignments were more likely to report higher job satisfaction. All variables showed statistically significant p-values (p < 0.05), with odds ratios indicating strong associations, particularly between working conditions and satisfaction. Conclusion: The study concludes that the team assignment method has a substantial influence on nurses’ job satisfaction. Effective implementation of this method—through improved supervision, fair task distribution, and supportive working environments—can enhance both nurse well-being and care quality.